Tingkat Kepuasan Pasien Peserta Badan Penyelenggara Jaminan Sosial Kesehatan Terhadap Pelayanan Tindakan Kemoterapi Di Rumah Sakit Ibnu Sina Makassar Juni Tahun 2019 - Dahliah Dahliah; Nevi Sulvita Karsa; Faisal Sommeng; Imran Safei; Ema Magfirah (Rumah Sakit Ibnu Sina, Makassar, 2021)
Background: Patient satisfaction is the first indicator of a hospital standard and a measure of servicequality. Understanding the needs and desires of the patient is important that affects patient satisfaction, tohelp improve the quality of health services, requiring the establishment of Social Security administeringAgency (BPJS) which is required to provide Satisfaction in patients. The services provided by the hospitalmust be qualified and meet the five dimensions of the main quality: tangibles, reliability, responsiveness,assurance, and Emphaty.Research aims: To determine the level of satisfaction of BPJS patients on the service of chemotherapy inIbn Sina Makassar Hospital in June year 2019.Research methods: This research is a descriptive draft study using a cross sectional approach. The samplesin this study were 54 people who meet the criteria for inclusion and exclusion. The data collectiontechniques used are questionnaire.Results of the study: according to the research results of BPJS patient satisfaction level of chemotherapy inthe hospital Ibn Sina Makassar, using the dimensions obtained in the dimension tangible 50% satisfied and50% very satisfied, on the reliability dimension 37 % were satisfied and 63% were very satisfied, on thedimension responsiveness 51.9% satisfied and 48.1% very satisfied, on the dimension of assurance 29.6%feel satisfied and 70.4% very satisfied, and on the dimension of Emphaty 38.9% feel satisfied and 61.1%feel very satisfied.Conclusion: The quality of service quality of tangible, reliability, responsiveness, assurance, and emphatyaffects the level of patient satisfaction of the participants of the Social security health provider to theMinistry of Action chemotherapy at the hospital Ibn Sina Makassar.